Trade and Industrialization in Developing Agricultural Economies - Vamvakidis, Athanasios (IMF Working Papers; Working Paper, 1999)
This paper examines the impact of international trade on industrialization in developing agricultural economies. The findings show that developing agricultural economies that increased their openness during 1970-95 experienced an increase in their share of industrial production at the expense of agricultural production. This is in contrast to what many policymakers in these economies have often argued when trying to promote industrialization by restricting trade. The paper presents an infant industry model with learning effects from imports of manufacturing products that is consistent with the supporting empirical results.